Seismic fragility of tall concrete wall structures in Malaysia under near-field earthquakes considering inadequate splice length - Masoomi, Mohammad Masoud (2020)
Malaysia is located in low to moderate seismicity region in terms of earthquake events and mostly engineers design the structures under the gravity and wind loads and for the most part they don’t consider the codes requirements for the seismic loads. In this study the seismic performance of tall concrete wall buildings under the near field earthquake considering inadequate lap splice length effects has been discussed. In this study two RC buildings (A & B) having same height and plan but different in configuration are selected. Each building has 25 stories with story height of 3.2 m. The first 5 storeys of the building A and the first 3 storeys of building B have been considered as parking areas. The structural system of the parking levels for both buildings consists of columns and beams while the structural system of the upper levels vary and contain only flat slab and shear walls without columns. Using ETABS software the failure mechanism, Inter-Storey drift demands as well as drift capacities of the two reference buildings have been obtained under a set of fifteen Near-Field earthquake records from the process of Incremental Dynamic Analysis (IDA). Four fragility curves have been generated for four 2D frames which were extracted from main 3D models. Eventually, it has been concluded from the fragility curves that inadequate lap splice compared with sufficient condition imposes considerable effects on seismic behaviour of the structures, which by reducing the ductility make the structures less resisting and prone to premature failure against earthquake excitations.